Local inflammatory factors in pregnant women with various methods of cervical insufficiency treatment - Chernega , Violetta; Bila , Victoria; Zahorodnia , Oleksandra (The Ukrainian Scientific Medical Youth Journal, 2024)
the reasons for the formation of cervical insufficiency are considred to be different from violation of the ratio of connective tissue elements due to its genetic characteristics to hormonal imbalance, and the predominance of pro-inflammatory factors of the immune system. A special attention is devoted to clinical situations, when cervical insufficiency was diagnosed in terms 22-24 weeks, the treatment means an alternative between emergency cerclage and obstetric pessary. The gaol of study – to compare dynamic of vaginal microbiota and local cervical immune factors by use of different cervical insufficiency treatment methods. Materials and methods. 81 pregnant with cervical insufficiency, diagnosed in term 22-24 weeks were observed, 47 pregnant treated by cerclage procedure (group A), and 34 were fitted with an obstetric pessary (group B). 30 healthy pregnant women in the period of 22 weeks formed group C. In all patients before treatment and every two weeks after it microscopy of vaginal discharges according to Hay/Ison criteria and evaluation of cervical cytokines were performed. Results. The balance by obstetric pessary use of type I and type III by Hay-Ison criteria being similar before treatment with pregnancy prolongation is changing dramatically to the prevalence of bacterial vaginosis be use of obstetric pessary – from 30,3% and 21,2% in 2 weeks to 25,0% and 41,7% in 6 weeks, by cerclage – from 43,5% and 14,9% in 2 weeks to 30,3% and 17,5% in 6 weeks. Patients with cervical insufficiency have increased concentration of IL-6 and IL-10, but by use of obstetrical pessary additionally growth of IL-8 from 42,3 pg/ml in 2 weeks to 187,6 pg/ml in 6 weeks is registered as well as decreasing of SLPI from 1,5 μg/ml to 0,6 μg/ml. Both changes show progression of inflammation and are associated with worth pregnancy outcomes. In the same time, cerclage is assocated with growth of SLPI from 1,9 μg/ml to 4,3 μμg/ml, what is a marker of adequate immune reaction by pregnancy. There is a difference between the groups of cerclage and obstetric pessary in dynamic of microbiota changes - a tendency to increasing of laboratory criteria of bacterial vaginosis frequency in group of obstetric pessary in 2 weeks becomes significant in 4 and more in 6 weeks comparing with group of cerclage. Proper to cervical insufficiency high concentration of proinflammatory IL-6 and IL-10 by use of obstetrical pessary is complicated by increasing of IL-8 and decreasing of SLPI, what means an activation of cervical inflammation, by cerclage – a increasing of SLPI is observed, what is favourable for pregnancy.